2014
DOI: 10.1002/ijch.201400057
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Amorphous Organic Semiconductors: Effects of Disorder, Carrier Density, Traps, and Scatters

Abstract: In real devices, organic semiconductors are largely amorphous. Because accurate molecular packing in them cannot be obtained, the relationship between the molecular structure and the material properties can be difficult to understand. Nevertheless, knowing the charge transport processes is essential to material and device engineering. In amorphous organic semiconductors, charge transport is often apprehended as a hopping process that can be described using the Marcus or MillerAbrahams equations. The intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 78 publications
0
28
0
1
Order By: Relevance
“…For the organic semiconductor sites, the site energy is assumed to have a Gaussian distribution, and the density of electronic states (DOS), g ( E ), writes asgE = 12πσ2exp E22σ2where σ is the energetic disorder. Typical values of the energetic disorder in organic semiconductors are in the range of 50–150 meV . In this study, we vary σ in the range of 51–103 meV, made to correspond to 2 k B T –4 k B T at room temperature (with T being the temperature and k B the Boltzmann constant).…”
Section: Methodsmentioning
confidence: 99%
“…For the organic semiconductor sites, the site energy is assumed to have a Gaussian distribution, and the density of electronic states (DOS), g ( E ), writes asgE = 12πσ2exp E22σ2where σ is the energetic disorder. Typical values of the energetic disorder in organic semiconductors are in the range of 50–150 meV . In this study, we vary σ in the range of 51–103 meV, made to correspond to 2 k B T –4 k B T at room temperature (with T being the temperature and k B the Boltzmann constant).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the thermal activation energy needed for the re-mobilization of trapped charge carriers is lowered in the presence of strong electrostatic fields. As a consequence, the immobilization of charge carriers is more prominent in case of rather weak fields, and the effective mobility of charge carriers increases with increasing field strength [15].The authors have observed the analogous effects in case of current transport through macroscopic dust layers as well [10,11].…”
Section: Mechanisms Of Charge Transportmentioning
confidence: 79%
“…In addition to the kinetic effects resulting from charge carrier trapping, detrapping and recombination, current transport through dielectrics is controlled by the space charge effect [10][11][12][13][14][15]. Each charge carrier, mobile or trapped, contributes to the space charge according to its polarity.…”
Section: Mechanisms Of Charge Transportmentioning
confidence: 99%
“…Benefitting from the suppressed hole trap, holes can be accumulated either on host or on dopant. After recombination with the injected electrons via an electrostatic attraction, two classes of excitons are able to be formed on both host and dopant, resulting in a dual emission and thus white EL ( Figure 4B) (Liu et al, 2005;Farmer et al, 2011;Li et al, 2014). To avoid the above-mentioned aggregation induced TTA in neat films, doped devices were further assembled with FIGURE 4 | Comparison of the EL spectra and proposed working mechanism between PCzDMPE-R5.0 (A) and D2-PCzDMPE-R5.0 (B).…”
Section: Electroluminescent Propertiesmentioning
confidence: 99%